Implementasi Deep Learning dalam Edukasi Lingkungan dan Kesadaran Ekologis pada Peserta Didik SMA Negeri 1 Siantan - Nafisatul Fuadah; Widia Nurmadyah (Yayasan Al-Afif, 2025)
The decline in biodiversity due to climate change, pollution, and deforestation necessitates active participation from the younger generation. This study aims to assess students' ecological awareness through a deep learning approach in schools, hypothesizing that its three key orientations can foster pro-environmental behavior. A mixed-methods approach was employed with a sample of 48 students. Data were collected through Likert-scale questionnaires and participatory observation. The results revealed: 0 students